Students' Views on Sex Offenders - Farhanah, Zahra; Mudinillah, Adam; Zubaidah, Zubaidah (Darussalam: Journal of Psychology and Educational, 2024)
Casual sex is a relationship driven by sexual desire, both with the opposite sex and the same sex, without any marriage ties, and can be carried out freely with many people. Adolescent problems are very complex problems, one of which is free sex. The problem of free sex is the most prohibited thing in Indonesia. In European countries this is normal or legal, but in Indonesia it is strictly prohibited. Even though there is no public law that regulates adultery between two single people. However, there are still customary laws that apply in Indonesia, so free sex is prohibited.